2019
DOI: 10.7554/elife.53400
|View full text |Cite
|
Sign up to set email alerts
|

Helix breaking transition in the S4 of HCN channel is critical for hyperpolarization-dependent gating

Abstract: In contrast to most voltage-gated ion channels, hyperpolarization- and cAMP gated (HCN) ion channels open on hyperpolarization. Structure-function studies show that the voltage-sensor of HCN channels are unique but the mechanisms that determine gating polarity remain poorly understood. All-atom molecular dynamics simulations (~20 μs) of HCN1 channel under hyperpolarization reveals an initial downward movement of the S4 voltage-sensor but following the transfer of last gating charge, the S4 breaks into two sub-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
51
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 85 publications
(134 reference statements)
9
51
1
Order By: Relevance
“…Consequently, the VSD was trapped in a presumably activated state, characterized by a kink in S4 at the level of the disulfide bridge and a sliding movement of the external part of S4 towards the intracellular side ( 25 ). Similar conformational changes were observed in MD simulations of the HCN voltage-sensor domain under membrane hyperpolarization ( 26 ). The breaking of the S4 helix in two smaller helices was suggested to be essential to hyperpolarization gating.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Consequently, the VSD was trapped in a presumably activated state, characterized by a kink in S4 at the level of the disulfide bridge and a sliding movement of the external part of S4 towards the intracellular side ( 25 ). Similar conformational changes were observed in MD simulations of the HCN voltage-sensor domain under membrane hyperpolarization ( 26 ). The breaking of the S4 helix in two smaller helices was suggested to be essential to hyperpolarization gating.…”
Section: Discussionsupporting
confidence: 75%
“…The resulting sliding movement of the kinked S4 helix towards the intracellular space provides a more consensual explanation to the avidin accessibility experiments. Similar conformational changes were recently observed in the VSD of HCN, a channel activated by hyperpolarization ( 25, 26 ). The breaking of S4 observed in the VSD of KvAP reveals that this transition is not specific to hyperpolarization gating.…”
Section: Introductionsupporting
confidence: 83%
“…Consistent with this hypothesis, coexpression of the PD with the VSD lacking the Cterminal end of the S4 resulted in cNMP modulated but voltage-independent channels (33) and cross-linking the S4 and S5 could lock the channels in the "locked-open" or "locked-closed" states (35,36). More recent structural analysis of the cross-linked HCN1 channels and molecular dynamics simulations indicated that during the hyperpolarization-dependent gating the S4 helix breaks into two helices (31,37). Since the HCND forms direct interactions with the VSD, it could also contribute to the VSD movement during the voltage-dependent gating.…”
Section: Discussionmentioning
confidence: 72%
“…Using a combination of long molecular dynamics (MD) simulations with the depolarized human HCN1 cryo-EM structure (Lee and MacKinnon, 2017) as template, as well as functional studies with HCN-eag chimeras, a hyperpolarizationinduced break in the S4 helix of the VSD was observed. This break originated two sub-helices and placing the lower sub-helix in an orientation almost parallel to the membrane plane as a surrogate S4-S5 helix (Kasimova et al, 2019). The breaking transition seemed to be important for HCN1 hyperpolarizationdependent activation.…”
Section: New Structural and Functional Data Regarding Allosteric Inflmentioning
confidence: 97%
“…The breaking transition seemed to be important for HCN1 hyperpolarizationdependent activation. Strikingly, the hydrophobicity of the amino acid following the breakpoint determined the gating polarity of some chimeric channels, changing it from a depolarization-to a hyperpolarization-dependent activation, opening the possibility that divergence of both types of channels could have occurred through a single point mutation in the S4 segment (Kasimova et al, 2019). The presence of the interfacial S4 sub-helix following the aforementioned S4 helix break, has been demonstrated in the recent cryo-EM structure of the HCN1 channel with the VSD chemically trapped in a hyperpolarized conformation by reversible, metal-mediated cross bridging (Lee and MacKinnon, 2019).…”
Section: New Structural and Functional Data Regarding Allosteric Inflmentioning
confidence: 99%